2023
DOI: 10.1039/d3nj00289f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Bz-TTFs with polymerization sites and the properties of Li-ion batteries comprising them as active materials

Aya Yoshimura,
Moeko Yoshinouchi,
Keisuke Hemmi
et al.

Abstract: We have found that benzene-fused TTFs bearing polymerization sites could prolong the cycle life of LIBs via “in-cell polymerization”.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In a previous study, we found that TTF-4TPA acts as an active material . CV of TTF alone and reports on molecules containing it suggest that it can act as an active material. However, the possible function of the TPA moiety as an active substance remains unclear, and its in-cell polymerization has not been reported. Therefore, the charge/discharge curves and cycle performance of the cell with TPA were investigated in a Li system, as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%
“…In a previous study, we found that TTF-4TPA acts as an active material . CV of TTF alone and reports on molecules containing it suggest that it can act as an active material. However, the possible function of the TPA moiety as an active substance remains unclear, and its in-cell polymerization has not been reported. Therefore, the charge/discharge curves and cycle performance of the cell with TPA were investigated in a Li system, as shown in Figure .…”
Section: Resultsmentioning
confidence: 93%